Lectoras y lectores digitales. Cualificación de la lectura crítica de contenidos digitales con estudiantes de séptimo grado (2023)
This study falls within the scope of educational research, with a specific focus on exploring and refining critical reading teaching practices. The relevance of this analysis lies in its application in contemporary educational environments, where the integration of technology and digital education play a crucial role. In order to address this complex task, the research is organized around various essential components, the analysis of which will contribute to a deeper understanding of the dynamics involved in the development of critical reading skills in the current educational context.